2004
DOI: 10.1007/978-3-540-25931-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring the Drawability of Extended Euler Diagrams for up to 8 Sets

Abstract: International audienceThis paper shows by a constructive method the existence of a diagrammatic representation called extended Euler diagrams for any collection of sets X1, ..., Xn , n < 9. These diagrams are adapted for representing sets inclusions and intersections: each set Xi and each non empty intersection of a subcollection of X1, ..., Xn is represented by a unique connected region of the plane. Starting with an abstract description of the diagram, we define the dual graph G and reason with the propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 7 publications
0
56
0
1
Order By: Relevance
“…Moreover, algorithms for automatically producing Euler diagrams, given the information to be visualized, are sought and a number of them now exist for the 2D case, including [3,7,8,14,16,17,19,24,25]. These algorithms require a description of a required diagram, d, to be provided which typically comprises precisely the descriptions of the zones in d.…”
Section: The Drawability Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, algorithms for automatically producing Euler diagrams, given the information to be visualized, are sought and a number of them now exist for the 2D case, including [3,7,8,14,16,17,19,24,25]. These algorithms require a description of a required diagram, d, to be provided which typically comprises precisely the descriptions of the zones in d.…”
Section: The Drawability Problemmentioning
confidence: 99%
“…If we want to enforce the unique labels property then we must allow the curves used in the Euler diagrams to be non-simple (i.e. they must be allowed to self-intersect) [9,24]. However, using either non-unique labels or self-intersecting curves brings with it usability weaknesses.…”
Section: Comparison: Everything Is Drawablementioning
confidence: 99%
“…For example, in [2] some well-formedness conditions are relaxed and the term Euler-like diagrams is adopted for variations such as allowing "holes". In [16] it is shown that all abstract diagrams for at most eight sets are drawable using such Euler-like diagrams. Recently, a methodology for generating general Euler diagrams has been developed [11], ensuring the production of a diagram, with a heuristic approach to repairing possible breaks in well-formedness.…”
Section: Coloured Euler Diagramsmentioning
confidence: 99%
“…Thus, for example, contours are not allowed 'to be tangential to' or 'to run along' one another -they must cross transversely. Other authors have made different choices as to which topological features are allowed [9,19,29,44].…”
Section: Concrete Spider Diagramsmentioning
confidence: 99%